Sosialisasi Literasi Keuangan Era Generasi Z di SMK Negeri 2 Penukal Kabupaten Pali Sumatera Selatan - Sri Porwani; Dian Utari; Iin Hendrayani; Faitullah Faitullah; Destia Aktarina; Ingge Rosalia Lahdau; Allya Tatalisa Rianda (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Financial literacy is an important skill for Generation Z, especially SMK students who are preparing to enter the workforce or continue their higher education. At SMK Negeri 2 Penukal, Pali Regency, South Sumatra, class XII students majoring in Software Engineering and Nursing Assistant wanted to improve their knowledge of finance through a community service program. The activity took place in a one-day intensive session, involving 50 students through an interactive approach that included lectures, group discussions, and practical workshops. With pre-test and post-test scores increasing by 38%, the evaluation results showed significant improvement. In addition, 85% of participants demonstrated basic skills in digital money management and a better understanding of investment basics. Despite the limited time, the program successfully provided Generation Z with essential financial decision-making skills, in line with their unique career prospects in technology and healthcare.